MEDICAL ETHICS AND PROFESSIONAL MISCONDUCT (Indian Internet Journal of Forensic Medicine and Toxicology, 2003)
Medicine and law have always been related to each other. Bonds that united them in ancient days were religion and superstitions. Written records of law medicine date back to 3-4 thousand years B.C. in Egypt, Babylon, Indian and China. The code of king of Babylon (about 2200 B.C.) is the oldest known media-legal code. Father of Modern medicine, Hippo crates (460-377 B.C.) was born and practiced in Greece. His contribution to medical ethics is by far the greatest. Around the banging of the Christian are various eugenic and public health provisions laid down in the Justinian code regulated the practice of medicine and surgery.
Keywords: Hippo crates; various eugenic